Relative Studies of Vibrational and Quantum Chemical Calculations on Some α, β-Unsaturated Esters and Related Molecule - Ajit, V.; Rajinder, S. (Journal of Scientific Research, 2023)
The paper presents a study on the vibrational spectra of four different compounds, namely, methyl acrylate (MA), methyl methacrylate (MMA), methyl trans crotonate (MTC), and methyl-3-methoxy-2-propenoate (MMP), in their electronic ground state using the Hartree-Fock and Density Functional Theory calculations with extended basis sets and polarization functions. The study compares the outcomes of the possible conformers in terms of their frequency, form, and intensity of vibrations, as well as the potential energy distribution across the symmetry coordinates in the ground state. Moreover, the study examines the relationship between bond length and bond order.